1982
DOI: 10.1111/j.1600-0722.1982.tb01521.x
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal effect of pooled human serum on Bacteroides melaninogenicus, Bacteroides asaccharolyticus and Actinobacillus actinomycetemcomitans

Abstract: – Bacteria belonging to the species B. melaninogenicus ss. melaninogenicus (two stains), B. melaninogenicus ss. intermedius (five strains), B. asaccharolyticus (seven strains), and Actinobacillus actinomycctemcomitans (four strains) were tested under anaerobic conditions for their sensitivity to the bactericidal effect of pooled human serum. The A. actinomycetemcomitans strains were not killed to any extent by the serum. Both B. melaninogenicus ss. melaninogenicus strains were killed by serum. The sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 37 publications
4
52
0
Order By: Relevance
“…P. gingivalis is resistant to killing by host complement, and it is believed that capsule plays a central role in the resistance (57,63). Since ⌬PG352 has a defective capsule, we hypothesize that the mutant might become sensitive to the complement killing.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…P. gingivalis is resistant to killing by host complement, and it is believed that capsule plays a central role in the resistance (57,63). Since ⌬PG352 has a defective capsule, we hypothesize that the mutant might become sensitive to the complement killing.…”
Section: Resultsmentioning
confidence: 95%
“…P. gingivalis is resistant to complement killing (63). Compared to the wild type, the ⌬PG352 mutant became more vulnerable to serum killing (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since the work of Sundqvist and Johansson (37) showed that Bacteroides asaccharolyticus, later reclassified as P. gingivalis, is resistant to killing by complement in serum, several groups have investigated the cause of this resistance. Sundqvist et al (38) showed that complement components are susceptible to degradation by protease(s) produced by P. gingivalis.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were harvested, washed once in complement fixation diluent (CFD) (tablet form; Oxoid), and adjusted to an optical density at 595 nm (OD 595 ) of 0.5 (approximately 10 7 CFU ml Ϫ1 ). Conditions for measurement of bacterial killing were established with P. melaninogenica, ATCC 25845, which has been shown to be sensitive to complement (37). Aliquots of 0.8 ml bacteria in triplicate were incubated anaerobically with 0.2 ml serum for 0 and 60 min and with heatinactivated serum for 60 min.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that most strains of P. gingivalis are resistant to the bactericidal lytic activity of human serum (14,15), and gingipains are implicated as the major factor exerting protection against complement. HRgpA cleaves purified C3 and C5, leading first to the release of active fragments such as C5a and C3b followed by degradation and loss of function by these complement factors (16).…”
mentioning
confidence: 99%